Effect of everolimus on skin lesions in patients treated for subependymal giant cell astrocytoma and renal angiomyolipoma: final 4‐year results from the randomized EXIST‐1 and EXIST‐2 studies. (16th July 2018) - Franz, D.N.; Budde, K.; Kingswood, J.C.; Belousova, E.; Sparagana, S.; de Vries, P.J.; Berkowitz, N.; Ridolfi, A.; Bissler, J.J.
Abstract: Background: Tuberous sclerosis complex (TSC) is a genetic disorder associated with tumour growth in various organs, including the brain, kidneys, heart and skin. Cutaneous lesions are prevalent manifestations of TSC, occurring in up to 90% of patients. Oral mammalian target of rapamycin inhibitors, such as everolimus, is believed to be effective for treatment of TSC‐associated lesions because they act on the underlying disease pathophysiology. Objective: We evaluated the long‐term effect of oral everolimus on TSC‐associated skin lesions as a secondary objective in the phase III studies EXIST‐1 (NCT00789828) and EXIST‐2 (NCT00790400) after approximately 4 years of treatment. Materials and methods: Everolimus was dosed 4.5 mg/m 2 /day (titrated to trough 5–15 ng/mL) in patients with TSC‐associated subependymal giant cell astrocytoma in EXIST‐1, and 10 mg/day initially in adult patients with TSC‐ or sporadic lymphangioleiomyomatosis–associated renal angiomyolipoma in EXIST‐2. Following positive results from the core phase, remaining patients were offered open‐label everolimus in an extension. Skin lesion response rate was the proportion of patients achieving complete or partial clinical response. Results: A total of 105 patients in EXIST‐1 and 107 in EXIST‐2 received everolimus and had ≥1 skin lesion at baseline. Skin lesion response rate (95% confidence interval) was 58.1% (48.1–67.7%) in EXIST‐1 and 68.2% (58.5–76.9%) in EXIST‐2; most were partial responses. At week 192 (EXIST‐1: n = 55; EXIST‐2: n = 56), 69% and 66% had a response. Most common drug‐related adverse event was stomatitis (41–45%). Conclusion: Oral everolimus improved TSC‐related skin lesions, with responses sustained over 4 years of treatment in EXIST‐1 and EXIST‐2.